Editorial (Revista Venezolana de Salud Pública, 2018)
With the publication of the Revista Venezolana de Salud Pública we propose to contribute to the construction of a scientific communication space for the dissemination of science in this field of such social relevance. With the effort of all the actors of the Venezuelan Public Health, but with the doors open to interaction with others in Latinamerica and the world we expect to open roads to the transmission of knowledge, promote analysis, discussion and the strengthening of our intellectual heritage as an information base for the preparation of scientifically and socially supported health policies.